2012
DOI: 10.22579/20112629.266
|View full text |Cite
|
Sign up to set email alerts
|

Requerimientos nutricionales para Tilapia del Nilo (Oreochromis niloticus)

Abstract: Recibido: marzo 22 de 2011Aceptado: marzo 09 de 2012 ResumenEsta revisión fue realizada con objetivo de acopiar información de los recientes avances sobre los requerimientos de algunos nutrientes para la tilapianilótica (Oreochromisniloticus). Los requerimientos de proteína bruta, están siendo substituidos por el requerimiento específico de aminoácidos, como en el caso de lisina y metionina, aplicando el concepto de proteína ideal. Los requerimientos nutricionales de tilapia delNilo sugeridos por NRC (1993), d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…Las exigencias nutricionales de los alevinos son iguales a la de las tilapias en términos cualitativos, sin embargo, en términos cuantitativos, las exigencias son mayores en peces jóvenes que en adultos [5] [6].…”
Section: Resultsunclassified
“…Las exigencias nutricionales de los alevinos son iguales a la de las tilapias en términos cualitativos, sin embargo, en términos cuantitativos, las exigencias son mayores en peces jóvenes que en adultos [5] [6].…”
Section: Resultsunclassified
“…(2012) [27] , mentioned that optimal protein level for Tilapia culture must be between 26.8 to 41.3% of protein, depending the life stage cycle. Likewise, Green et al (2019) [28] , found out in a Biofloc system which cultured hybrid tilapia (O. aureus x O. niloticus), that the protein diet content can be reduced to 27.7% without affecting productivity due to the use of microbial flocks as diet.…”
Section: Tilapiamentioning
confidence: 99%
“…Tilapia Oreochromis niloticus is valued in aquaculture because of its fast growth, disease tolerance, and other biotic and abiotic factors, which makes it a highly deman-ded species (Castillo-Juárez et al, 2009;Torres et al, 2012). Another advantage is that this species is omnivorous, whose feeding may include proteins, carbohydrates, vegetable oils, aquatic plants, animal by-products, fermented yeasts, and in some cases agroindustrial by-products in commercial feeds (González-Salas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%